Hambatan Dalam Upaya Pengembangan Motorik Kasar Anak Usia 5-6 Tahun - Sudirman; Hadlun; Hultasari; Siti Mariana (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2023)
This research is located in Subulussalam nw serage Kindergarten which is motivated by the problem of Gross Motor Development of Children in Throwing and Kicking Ball Games. This study uses a qualitative approach by determining the research subject using snowball sampling technique. Data collection techniques were carried out using observation, interview, and documentation techniques. Data analysis techniques included data reduction, data presentation, and verification/drawing conclusions, while the data reliability test was carried out by extending participation, observation accuracy, triangulation and consulting supervisors. The results of the study showed that there were some children in Kindergarten Subulussalam nw serage who did not want to take part in learning activities about gross motor skills in throwing and kicking balls, the problem was that the children were too quiet and did not want to socialize with their friends, and also the children preferred to play alone rather than playing ball. with his friends. And also, the child's parents don't want their child to participate in the learning activities of throwing and kicking the ball because the parents are afraid if their child is hit by a ball.